(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
The Mucopolysaccharidosis [MPS] are a group of orphan or rare genetic diseases characterized by lysosomal storage disorders which are recognized by bone malformations and neuropsychological implications that have not been studied so far. For this reason, the first cross-sectional descriptive study of neuropsychological nature was conducted on variants of the disease, Hunter Syndrome [MPS II], Morquio A Syndrome [MPS IV A] and Maroteaux-Lamy syndrome [MPS VI] in 21 children and adolescents aged 3 to 19 years old, at the Colombian Association of Patients with Lysosomal Storage Diseases [ACOPEL, for its Spanish acronym] in Bogotá, Colombia. Results indicate that for the different types of MPS tested is not easy to make a neuropsychological characterization and generalize these results to other populations. However, MPS type II shows moderate to severe cognitive deficit with a compromise in psychomotor development. Morquio A presents average intelligence, and MPS type VI points to deficits partially related to sensory impairment, implying significant differences between them. It is important to continue carrying on this type of studies to achieve a better classification of these diseases according to their cognitive functioning from the neuropsychological perspective.